Arab worlds beyond the Middle East and North Africa - Alkazemi, Mariam; Youakim, Claudia E., 1979- (Lexington Books, 2021)
"By providing migration experiences of Arabs to various nation-states, this volume examines socio-historical factors that allowed Arab communities to settle in several places, including Latin America, Asia, the United States, Europe and Africa. It bridges several fields to provide context that is useful in today's globalized world"--